2023
DOI: 10.3390/app13031601
|View full text |Cite
|
Sign up to set email alerts
|

Archaeoseismological Evidence of Seismic Damage at Medina Azahara (Córdoba, Spain) from the Early 11th Century

Abstract: The “Caliphal City of Medina Azahara” was built in 936–937 CE or 940–941 CE (depending on the source) by the first Caliph of al-Andalus Abd al-Rahman III, being recently inscribed (2018) on the UNESCO World Heritage List. The abandonment and destruction of the city have been traditionally related to the civil war (“fitna”) that started between 1009 and 1010 CE. However, we cannot rule out other causes for the rapid depopulation and plundering of the city just a few decades after its foundation. The archaeoseis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Several studies have reported the several types of damage to historical buildings caused by earthquakes [9,13,14,54,58,63,69,[124][125][126][127][128][129][130][131][132][133]. The type of damage, such as, for example, displaced tilted walls, is dependent on the orientation of the wall with respect to the horizontal component of the seismic waves [14,62,66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the several types of damage to historical buildings caused by earthquakes [9,13,14,54,58,63,69,[124][125][126][127][128][129][130][131][132][133]. The type of damage, such as, for example, displaced tilted walls, is dependent on the orientation of the wall with respect to the horizontal component of the seismic waves [14,62,66].…”
Section: Discussionmentioning
confidence: 99%
“…The type of damage, such as, for example, displaced tilted walls, is dependent on the orientation of the wall with respect to the horizontal component of the seismic waves [14,62,66]. The orientation of the fallen columns depends on the propagation direction of the seismic waves [14,15,96,129,130].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation